2014
DOI: 10.1021/la502315m
|View full text |Cite
|
Sign up to set email alerts
|

A Nonenzymatic Biosensor Based on Gold Electrodes Modified with Peptide Self-Assemblies for Detecting Ammonia and Urea Oxidation

Abstract: We have developed a nonenzymatic biosensor for the detection of ammonia and urea oxidation based on the deposition of peptide microstructures onto thiolated gold electrodes. FF-MNSs/MCP/Au assemblies were obtained by modifying gold substrates with 4-mercaptopyridine (MCP), followed by coating with l,l-diphenylalanine micro/nanostructures (FF-MNSs) grown in the solid-vapor phase. Benzene rings and amide groups with peptide micro/nanostructures interact with synthetic NH4(+) receptors through cation-π and hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 61 publications
3
50
0
Order By: Relevance
“…The results confirmed that the hexagonal phase is indeed P61, and the orthorhombic is P22121, 8,20 as shown in Figure 2A. By means of Rietveld refinements ( Figure S1-S4, presented as Supporting Information material), 37, 38 the presence of MP11 was clearly evidenced and the main characteristic peaks -found in both phases -are indicated by arrows in Figure 2A.…”
Section: Spectroscopic Characterizationsupporting
confidence: 67%
See 3 more Smart Citations
“…The results confirmed that the hexagonal phase is indeed P61, and the orthorhombic is P22121, 8,20 as shown in Figure 2A. By means of Rietveld refinements ( Figure S1-S4, presented as Supporting Information material), 37, 38 the presence of MP11 was clearly evidenced and the main characteristic peaks -found in both phases -are indicated by arrows in Figure 2A.…”
Section: Spectroscopic Characterizationsupporting
confidence: 67%
“…Another scenario is that since PAH does not cover the FF-MNSs it is more susceptible to dissolution, as seen in some reports where FF-MNSs dissolves in phosphate buffer solution. 8,[49][50][51] Following the characterization, the kinetics of the reaction can be described by the equation (6):…”
Section: Kinetics Analysis Of the H2o2 Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This contribution is actually the first to report a novel electrochemical biosensor for measurement of whole‐blood heparin based on heparin‐binding peptide. In recent years, peptides have been used frequently for biosensor fabrication because of their potent binding affinity towards specific analytes, high biological compatibility, and high solubility in aqueous solutions . Heparin specialized binding peptide from the G domain of the laminin α1 chain has been rationally designed to construct the electrochemical biosensor, which exhibits considerable binding affinity and specificity towards heparin …”
Section: Methodsmentioning
confidence: 99%